2017
DOI: 10.1088/1752-7163/11/1/016003
|View full text |Cite
|
Sign up to set email alerts
|

Fatty acid derivative, chemokine, and cytokine profiles in exhaled breath condensates can differentiate adult and children paucibacillary tuberculosis patients

Abstract: The anti-mycobacterial immune response in adults and children with tuberculosis (TB), as well as the response in bacteriologically positive and negative patients, is different. However, knowledge of the immunological events occurring in the lungs in these clinical situations remains scarce. Exhaled breath condensate (EBC) samples may be useful for studying the inflammatory environment of the lower airways in TB patients. The fatty acid, cytokine, and chemokine profiles in EBC from healthy adults; smear-positiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 58 publications
0
8
0
4
Order By: Relevance
“…Exploration of multiple host proteins as surrogates of TB disease is often used for the immunodiagnosis of TB (10) and monitoring of treatment responses (25). Several exploratory inflammatory (26) and metabolic (27) markers have been used to identify disease signatures among children. Among these, the use of serum biomarkers and CRP alone (28) or in combination with other proteins (24,26) resulted in good accuracy in discriminating TB and monitoring responses after anti-TB treatment (25).…”
Section: Discussionmentioning
confidence: 99%
“…Exploration of multiple host proteins as surrogates of TB disease is often used for the immunodiagnosis of TB (10) and monitoring of treatment responses (25). Several exploratory inflammatory (26) and metabolic (27) markers have been used to identify disease signatures among children. Among these, the use of serum biomarkers and CRP alone (28) or in combination with other proteins (24,26) resulted in good accuracy in discriminating TB and monitoring responses after anti-TB treatment (25).…”
Section: Discussionmentioning
confidence: 99%
“…En nuestro grupo de investigación (Grupo de Inmunología Celular e Inmunogenética -GICIG) hemos utilizado otros componentes no volátiles en los exhalados respiratorios recolectados utilizando los denominados «tubos R» (véase figura 9) que han permitido diferenciar, por medio de cromatografía de gases, los pacientes paucibacilares de los pacientes bacilíferos e individuos sanos, con una efectividad del 100%. Entre estos componentes se han encontrado el ácido oleico y la quimioquina CCL-2, lo cual parece ser promisorio para ser usado como un potencial método de diagnóstico [164].…”
Section: Detección De Compuestos Volátiles Orgánicos En Exhalados Respiratoriosunclassified
“…A partir de cultivos micobacterianos se han detectado y diferenciado cepas de Mycobacterium con base en sus ácidos grasos, los cuales son liberados con hidróxido de potasio en agua-metanol, derivatizados con p-bromofenacil, bicarbonato de sodio y cloroformo y luego inyectados en el cromatógrafo líquido de alta eficacia para su detección [164,[171][172][173]. La HPLC también ha sido usada para la detección de ácido tuberculoesteárico en plasma por Traunmuller y colaboradores (2003) [174], quienes detectaron concentraciones más altas de este componente derivatizado con el reactivo fluorescente hidracida ácida 6,7 dimetoxi-1-metil-2(1H)-quinoxalinona-3-propionilcarboxílico (DMEQ-hidracida) en pacientes con tuberculosis activa, que fue confirmada por cultivo (n=125), en comparación con pacientes con enfermedades pulmonares no tuberculosas (n=116) e individuos sanos (n= 102).…”
Section: Detección Por Hplcunclassified
“…Insufficient number or dysfunction of T lymphocytes and macrophages, and the lack of related cytokines may lead to decreased immunity to Mtb. Therefore, immune status is closely related to the occurrence, development, and therapeutic response to TB (Grover et al, 2014;Mosquera-Restrepo et al, 2017). In recent years, it has been found that some antibacterial drugs not only kill pathogens but also regulate immune function during treatment (Hamilton-Miller, 2001;Schultz, Speelman, van der Poll, 2001;Tauber, Nau, 2008).…”
Section: Introductionmentioning
confidence: 99%